Pendampingan Kuliah Kerja Nyata (KKN) dengan Metode Penyuluhan untuk Pengembangan Potensi Desa Pasirbiru, Kecamatan Rancakalong - Riki Ruswandi; Aghitsna Fadhilah; Ahmad Maulana Andrian; Alfiani Octafiani; Andini Yuliani; Dika Arman Nuralamsyah; Fadhil Alwan Abdul Zalil; Iwan Satriyo Nugroho (Politeknik Piksi Ganesha Indonesia, 2025)
Waste, freshwater fisheries, Liquid Organic Fertilizer, this program aims to support the development of local potential, such as agriculture, Micro Small Medium Enterprises (MSMEs), and village culture, by actively involving the community at every stage. Thru socialization, training, and mentoring, students provide practical education related to organic farming, digital marketing, and business management. The results show an increase in community capacity, the formation of local extension agent cadres, and a growing interest among MSME actors in utilizing social media for promotion. The extension method has proven effective in building awareness, skills, and community ownership of development programs. This activity not only has a direct impact on improving welfare but also strengthens the partnership between universities and villages. Community Service Program based on counselling in Pasirbiru Village has become a strategic model in strengthening the village's potential sustainably.